An Optimized Flexible Accelerator for Elliptic Curve Point Multiplication over NIST Binary Fields - Amer Aljaedi; Muhammad Rashid; Sajjad Shaukat Jamal; Adel R. Alharbi; Mohammed Alotaibi (Applied Sciences, 2023)
This article proposes a flexible hardware accelerator optimized from a throughput and area point of view for the computationally intensive part of elliptic curve cryptography. The target binary fields, defined by the National Institute of Standards and Technology, are <semantics>GF(2163)</semantics>, <semantics>GF(2233)</semantics>, <semantics>GF(2283)</semantics>, <semantics>GF(2409)</semantics>, and <semantics>GF(2571)</semantics>. For the optimization of throughput, the proposed accelerator employs a digit-parallel multiplier. The size of the digit is 41 bits. The proposed accelerator has reused the multiplication and squaring circuit for area optimization to compute modular inversions. Flexibility is included using three additional buffers on top of the proposed accelerator architecture to load different input parameters. Finally, a dedicated controller is used to optimize control signal handling. The architecture is modeled using Verilog and implemented up to the post-place-and-route level on a Xilinx Virtex-7 field-programmable gate array. The area utilization of our accelerator in slices is 1479, 1998, 2573, 3271, and 4469 for <semantics>m=163</semantics> to 571. The time needed to perform one-point multiplication is 7.15, 10.60, 13.26, 20.96, and 30.42 μs. Similarly, the throughput over area figures for the same key lengths are 94.56, 47.21, 29.30, 14.58, and 7.35. Consequently, achieved results and a comprehensive performance comparison show the suitability of the proposed design for constrained environments that demand throughput/area-efficient implementations.